High entropy austenitic stainless steel and its manufacturing method
A high entropy austenitic stainless steel with controlled elemental ratios and a refined manufacturing process achieves both high strength and plasticity, addressing the limitations of conventional steels and reducing production costs.
Patent Information
- Application Number
- JP2023563148
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-23
- Filing Date
- 2022-10-31
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-10-31
AI Technical Summary
Existing commercial austenitic stainless steels face challenges in achieving a balance of high strength and high plasticity, with conventional methods often leading to significant loss of plastic toughness during grain refinement for strength improvement, and the use of high-entropy alloys with cobalt is costly and impractical for large-scale applications.
A high entropy austenitic stainless steel composition with controlled atomic percentages of Cr, Ni, Ti, and Al, along with an Fe base, and a manufacturing process involving vacuum melting, cold and hot rolling, and aging treatment, to form fine nanoprecipitated phases for enhanced strength and plasticity without cobalt.
The resulting stainless steel exhibits high strength and plasticity, with improved corrosion resistance and reduced production costs, outperforming conventional steels in mechanical performance and expanding application potential.
Smart Images

Figure 0007601463000002 
Figure 0007601463000003 
Figure 0007601463000004
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of materials, specifically to the field of stainless steel material technology, and more particularly to high-entropy austenitic stainless steel and a manufacturing method thereof. [Background technology]
[0002] Stainless steels are widely used in many industrial fields such as aviation, space, marine and nuclear industries due to their good corrosion and oxidation resistance, but all currently commercial stainless steels have difficulty in combining excellent strength and high plasticity. For example, austenitic stainless steels have good plasticity but too low strength. Ferritic stainless steels and martensitic stainless steels have somewhat high strength but general plasticity. Precipitation hardening stainless steels have the highest strength among stainless steel types but the lowest plasticity. At present, the austenitic stainless steels commonly used on the market are 201, 301, 304, 316 and other stainless steels with low strength and excellent plasticity and their derived materials, whose mass composition ratios of chemical elements are as follows: C≦0.15%, Si≦2.0%, Mn≦2.0% (in 201, 202: 5.0%≦Mn≦10.5%, each composition is different), P≦0.045%, S≦0.03%, N≦0.025%, 15.0%≦Cr≦28.0%, 3.5%≦Ni≦36.0 (Cr, Ni content is related to each system), and the rest are trace doping elements such as Cu, Nb, W, Ta, B and Al, as well as iron and other unavoidable impurities.
[0003] In recent years, researchers have used strong plastic deformation methods, such as liquid nitrogen cold rolling, mechanical alloying, high pressure torsion and extrusion, which can reverse martensite to austenite to refine the grain size of the material to the nano level and effectively improve the strength of the material. Although grain refinement has a significant effect of strengthening the strength, it also greatly reduces the plastic toughness of the material. In the field of materials science, a new metal material has emerged in recent years, which is called high entropy alloy or multi-component alloy. High entropy alloys contain at least five major elements, and the content of each element is 5-35at%. High entropy alloys have excellent properties that cannot be achieved by traditional alloys, such as high hardness, high strength, anti-oxidation, corrosion resistance, fatigue resistance, high temperature softening resistance, creep resistance, wear resistance, inherent magnetism, and excellent low temperature mechanical properties. CT Liu et al. introduced a design method to strengthen FeCoNiTiAl high entropy alloys using L12-Ni3(TiAl) precipitates, and by introducing L12-Ni3(TiAl) precipitates into a multi-component alloy substrate, the material strength is significantly improved and there is almost no loss of tensile plasticity [Science, 2018, 362, 933-937]. In this method, the strength is improved by introducing high-density nano-precipitates, and in the tensile deformation process, the interaction between dislocations and precipitates is a shear relationship, forming a large number of microstrips during deformation, thereby maintaining high plasticity. Therefore, the introduction of fine and high-density nano-precipitates into the substrate alloy plays an important role in strengthening structural materials. However, this high entropy alloy contains the expensive strategic metal cobalt, making it difficult to apply in large quantities. Therefore, it is extremely necessary to develop a novel, high-entropy austenitic stainless steel that does not contain elemental cobalt to fill the technical bottleneck of the incompatibility between strength and plasticity in conventional commercial austenitic steels and achieve strength-plasticity matching far beyond that of conventional austenitic stainless steels. Summary of the Invention
[0004] The component ratio of the medium-high entropy austenitic stainless steel in the present invention is mainly designed based on the following ideas: (1) The addition of Cr can improve the strength of stainless steel and ensure its corrosion resistance at the same time. The high Cr content contributes to its suitability for use in nuclear material environments (such as supercritical water and lead-bismuth solutions). (2) The addition of Ni element can expand the phase region in which nano-precipitates form and suppress the formation of other harmful intermetallic compounds that cause embrittlement. (3) The addition of an appropriate amount of Al element not only imparts oxidation resistance and corrosion resistance to the alloy, but also promotes the precipitation of nano-precipitates and allows the nano-precipitates to maintain high coherence with the substrate. (4) The addition of an appropriate amount of Ti element can refine the crystal grains and homogenize the structure, while at the same time forming nano-precipitates with Ni and Al to improve the strength of stainless steel. At the same time, Ti can replace expensive Cu, Co, Nb and Mo, reducing production costs, while not destroying the microstructure of the nano-precipitates. (5) Mn has a volatilization problem during the smelting process, which brings inconvenience to the alloy production and causes a large waste. The presence of Cu can cause the material to segregate and lead to inhomogeneity in the structure. Therefore, the alloy of the present invention needs to remove these two elements. (6) The rule of change of each element content in the alloy is as follows: The content of Ti, Al is determined by the content of the other three elements. When the content of Cr, Ni is higher than the content of Ti, Al, the content of Ti, Al needs to be appropriately reduced. When the content of Cr, Ni is lower than the content of Ti, Al, the content of Ti, Al needs to be appropriately increased. When the content of Cr element is high, the content of Ni element needs to be increased at the same time, which can on the one hand ensure that the substrate is austenitic structure, and on the other hand ensure that sufficient Ni atoms form nano-precipitate phase.
[0005] In order to solve the shortcomings of the prior art, the present invention aims to provide a high-strength, high-plasticity, high-entropy austenitic stainless steel and a manufacturing method thereof, and the technical means adopted by the present invention are as follows: A high entropy austenitic stainless steel, characterized based on atomic percentage content, the elemental composition of said stainless steel is as follows: Cr: 5~30%; Ni: 5~50%; Ti: 1~15%; Al: 1~15%; the balance is Fe. Preferably, based on atomic percentage content, the elemental composition of said stainless steel is as follows: Cr: 5~19%; Ni: 5~29%; Ti: 6~15%; Al: 5~15%; the balance is Fe.
[0006] Furthermore, the size of the nano-precipitates in the above stainless steel is ≦30 nm, and the number density of the nano-precipitates is ≧5.0×10 21 m -3 It is.
[0007] A method for producing high-entropy austenitic stainless steel, the specific steps of which are as follows: mixing the raw materials according to the atomic ratio requirements, obtaining an ingot by melting and pouring in a vacuum argon arc furnace, and then solution treating the ingot, followed by (1) cold rolling and recrystallization or (2) hot rolling, cold rolling, recrystallization, and aging treatment to obtain high-entropy austenitic stainless steel.
[0008] Furthermore, the cold rolling process in the above (1) is as follows: the reduction amount of each pass does not exceed 0.2 mm, and the total reduction amount is 60% to 70%.
[0009] Furthermore, the hot rolling and cold rolling processes in the above (2) are as follows: hot rolling is performed at 800°C to 1150°C, the reduction amount of each pass does not exceed 0.5mm, and the temperature during hot rolling is ensured to be within the 800-1150°C range. If the temperature drops, it can be returned to the furnace and kept warm for 5-15 minutes within the rolling temperature range. After the total reduction amount is 50% to 60%, it is switched to the cold rolling process, and the reduction amount of each pass of cold rolling does not exceed 0.2mm, and the total reduction amount is 60% to 70%.
[0010] Furthermore, the specific operation of the above recrystallization is as follows: (1) or (2) keep the rolled ingot at 1140°C to 1160°C for 1 to 3 minutes (if the volume of the ingot is too large, the recrystallization time can be increased appropriately). Preferably, the temperature increase rate for the recrystallization is 10° C. / min to 20° C. / min.
[0011] Furthermore, in the above-mentioned vacuum argon arc furnace melting process, the argon arc furnace is 5.0 × 10 -3 Fill the furnace with argon gas at a pressure of 5.0 x 10 Pa or less. 3 Pa, if the oxygen and nitrogen contents in the furnace are less than 0.002% within 180 minutes, smelting is started. Further, it includes removing oxygen with pure Ti before starting the melting process. Furthermore, the mass of the above pure Ti is 30-40 g, and it is not used as a raw material and is not involved in the melting process. Preferably, the number of melting cycles in the vacuum argon arc furnace is at least four.
[0012] The specific procedure for the solution treatment is as follows: The ingot after pouring is immersed in 1.0×10 -3 Heat to 1140°C to 1160°C at or below Pa, hold for 1 to 2.5 hours, then water quench or cool in air. The temperature rise rate in the solution treatment is preferably 10° C. / min to 20° C. / min.
[0013] Furthermore, the specific operation of the above aging treatment is as follows: the ingot after the recrystallization is kept at 500°C to 600°C for 0.5 to 1.5 hours, and then water quenched or air cooled. The temperature rise rate in the aging treatment is preferably 5° C. / min to 15° C. / min. Effect of the Invention
[0014] (1) The present invention provides a high entropy austenitic stainless steel, calculated in atomic percentage content, with the atomic composition ratio of each element being Cr: 5-30%, Ni: 5-50%, Ti: 1-15%, Al: 1-15%, and the balance being Fe and other unavoidable and very small impurity elements (C, N, O, etc.) introduced during smelting or heat treatment. The stainless steel component system is simple, reducing some precious metals and trace amounts of doping elements, and minimizing the addition of alloying elements. By using only five alloying elements (three major elements: Fe, Cr, Ni, and two minor elements: Ti and Al) and adjusting the atomic occupancy ratio of each component, the maximum amount of nano-precipitate phase is precipitated, and the high entropy austenitic stainless steel produced has high strength and high plasticity.
[0015] The addition of Cr improves the strength and corrosion resistance of stainless steel. The addition of Ni expands the phase region in which the nano-precipitate phase is formed, and inhibits the formation of harmful intermetallic compounds. The addition of Al imparts oxidation resistance and corrosion resistance to the material, and contributes to the formation of nano-precipitate phases. The addition of Ti element refines the grains and makes the structure uniform, while at the same time forming nano-precipitate phases with Ni and Al to improve the strength of stainless steel, and at the same time Ti replaces expensive Cu, Co, Nb, and Mo to reduce production costs and not destroy the microstructure of the nano-precipitate phase. The stainless steel has a base of Fe~Cr~Ni, and by controlling the content of Cr and Ni, the content of the two added elements Ti and Al is adjusted to form nano-precipitate phases to strengthen the base. Here, when the content of Cr element is high, the content of Ni element needs to be increased to ensure that the base is austenitic structure, while ensuring that sufficient Ni atoms form nano-precipitate phases, and at the same time, the content of Ti and Al can be appropriately reduced to prevent the formation of brittle intermetallic compounds, and vice versa.
[0016] In a preferred embodiment, the composition is Cr: 5-19%, Ni: 5-29%, Ti: 6-15%, Al: 5-15%, and the balance is iron. On the premise of ensuring the strength and plasticity of the alloy, the amounts of Cr and Ni used are reduced, and further the production cost is reduced.
[0017] (2) The present invention further provides a manufacturing process for high-strength, high-plasticity, high-entropy austenitic stainless steel, which simplifies the heat treatment process and reduces production costs. The manufacturing process is simple and has a wide range of application prospects. The solution treatment method in the present invention allows the alloying elements to be fully dissolved in the austenitic matrix, making the alloying components more uniform, and adopts high-temperature, short-time recrystallization treatment to obtain uniform and relatively coarse equiaxed grains, ensuring the good plasticity of the alloy, while greatly improving production efficiency and saving costs.
[0018] In one preferred embodiment of the present invention, a rolling process of hot rolling followed by cold rolling is adopted, which helps to solve the problem of the difficulty of rolling large ingots. Hot rolling can eliminate early rolling cracks, reducing the risk of subsequent cold rolling. Subsequent aging treatment contributes to maximized precipitation of nano-strengthening phases, thereby improving the strength and plasticity of the stainless steel. The stainless steel produced by the method of the present invention has excellent strength and plasticity combined, which makes it superior to most commercial stainless steels in terms of mechanical performance and applicable to most stainless steel service fields. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is an X-ray diffraction diagram of the high-entropy austenitic stainless steel Fe47Cr16Ni26Ti6Al5. [Diagram 2] FIG. 2 shows a transmission electron microscope image and element distribution diagram of the high-entropy austenitic stainless steel Fe47Cr16Ni26Ti6Al5. [Diagram 3] FIG. 3 is an engineering stress-strain curve of a high-entropy austenitic stainless steel measured at room temperature. [Figure 4]FIG. 4 is a comparative diagram comparing the yield strength ReL and fracture elongation E, which are the performance of commercial stainless steels in the prior art, with the mechanical performance of the high-entropy austenitic stainless steel of the present invention (here, the two-phase is ferrite + martensite, and the meaning of the two-phase in the following will be the same). [Diagram 5] FIG. 5 is a comparison diagram of the mechanical properties of the tensile strength Rm and the fracture elongation E of the high-entropy austenitic stainless steel of the present invention with the performance of commercial stainless steels in the prior art. [Figure 6] FIG. 6 is a comparison diagram of the yield strength and strength-ductility balance (tensile strength x fracture elongation) of the mechanical performance of commercial stainless steels in the prior art and the high-entropy austenitic stainless steel of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] In order to make the present invention more clearly understandable, the present invention will be further described with reference to the following examples and drawings.The examples are merely illustrative and do not limit the present invention in any way.In the examples, each original reagent material is commercially available, and the experimental method without specific conditions is the conventional method and conditions well known in the art, or follows the conditions recommended by the device manufacturer.
[0021] Example 1 This embodiment provides a high entropy austenitic stainless steel, the chemical composition of which is as follows: Fe 47 Cr 16 Ni 26 Ti6Al5 (atomic ratio) or Fe 48.56 Cr 15.39 Ni 28.24 Ti 5.32 Al 2.5 (weight ratio), and the effect on the material properties of very small amounts of impurity elements (C, N, O, etc.) that are inevitably mixed in during the smelting and heat treatment processes can be ignored.
[0022] The manufacturing steps of the high entropy austenitic stainless steel are as follows: (1) Based on the design ratio of the chemical components, each raw material was weighed and mixed (the purity of each raw material was ≥ 99.9%), and the mixture was heated in an argon arc furnace at 5.0 × 10 -3 Fill the furnace with argon gas at a pressure of 5.0×10 Pa or less. 3 After the pressure is adjusted to 1 Pa, the oxygen content and nitrogen content in the furnace are less than 0.002% within 180 minutes. First, 30 g of pure Ti is melted and deoxidized before starting the melting process. The melting process is carried out six times in an argon arc furnace, and the resulting ingot is cast into a sheet-shaped ingot of 60 x 10 x 5 mm. The chemical composition of the resulting ingot is the same as that of the high-entropy austenitic stainless steel. (2) The above ingot is placed in a furnace to undergo solution treatment and homogenization treatment, and then heated to 1150°C at a rate of 15°C / min, kept at that temperature for 120 minutes, and then water quenched. The ingot after solution treatment is subjected to a cold rolling deformation process. The rolling process is as follows: the reduction in each pass does not exceed 0.2mm, and the total reduction is 66.7%. The rolled ingot is heated to 1150°C at a rate of 10°C / min, kept at that temperature for 1.5 minutes to complete recrystallization. The ingot after recrystallization is heated to 600°C at a rate of 10°C / min, kept at that temperature for 1 hour, and then water quenched to complete the aging treatment. Diffraction was performed using conventional CuKα radiation as the X-ray source, and the diffraction spectrum was obtained as shown in Figure 1. The diffraction peaks in the figure can be localized to the (111), (200), (220), (311), and (222) diffraction peaks of the face-centered structure, so the obtained structure is austenite, and the size of the nano-precipitate phase is too small to show any visible diffraction peaks in the X-ray diffraction diagram.
[0023] Example 2 This embodiment provides a high entropy austenitic stainless steel, the chemical composition of which is as follows: Fe 47 Cr 16 Ni 26 Ti6Al5 (atomic ratio) or Fe 48.56 Cr 15.39 Ni 28.24 Ti 5.32 Al 2.5(weight ratio), and the effect on the material properties of very small amounts of impurity elements (C, N, O, etc.) that are inevitably mixed in during the smelting and heat treatment processes can be ignored.
[0024] The manufacturing steps of the high entropy austenitic stainless steel are as follows: (1) Based on the design ratio of the chemical components, each raw material was weighed and mixed (the purity of each raw material was ≥ 99.9%), and the mixture was heated in an argon arc furnace at 5.0 × 10 -3 Fill the furnace with argon gas at a pressure of 5.0×10 Pa or less. 3 After the pressure is adjusted to Pa, the oxygen and nitrogen contents in the furnace are less than 0.002% within 180 minutes. First, melt 30g of pure Ti and deoxidize it before starting the melting process. Melt it six times in an argon arc furnace and cast it into a sheet-shaped ingot of 60×10×5mm. The chemical composition of the ingot is the same as that of the high-entropy austenitic stainless steel mentioned above. (2) The above ingot is placed in a furnace for solution treatment and homogenization treatment, and then heated to 1150°C at a rate of 15°C / min, kept at 40°C for 120 minutes, and cooled in air. The ingot after solution treatment is subjected to a deformation process of hot rolling followed by cold rolling. The rolling process is as follows: the hot rolling temperature is 1150°C, and the temperature is ensured to be within the 800-1150°C range during hot rolling. When the temperature drops, it is returned to the furnace and kept at the rolling temperature range for 5-15 minutes, and the reduction amount of each pass does not exceed 0.5mm, and the cold rolling process is switched to after the total reduction amount reaches 50%, and the reduction amount of each pass does not exceed 0.2mm, and the total reduction amount is 66.7%. The rolled ingot is heated to 1140°C at a rate of 15°C / min, and kept at 40°C for 1.5 minutes to complete recrystallization. The recrystallized ingot is heated to 550°C at a rate of 15°C / min, kept at that temperature for 1.5 hours, and then cooled in air to complete the aging treatment.
[0025] The material was characterized by transmission electron microscopy, and the transmission electron micrograph and element distribution map are shown in Figure 2. A large amount of spherical nano-precipitates were distributed in the stainless steel substrate, with the composition Ni-Ti-Al, the crystal structure face-centered cubic, the average size 14.4 nm (diameter), and the number density 1.68 × 10 22 m -3 It is.
[0026] Example 3 This embodiment provides a high entropy austenitic stainless steel, the chemical composition of which is as follows: Fe 39 Cr 20 Ni 30 Ti6Al5 (atomic ratio) or Fe 40.33 Cr 19.25 Ni 32.6 Ti 5.32 Al 2.5 (weight ratio), where the influence of unavoidable and extremely small amounts of impurity elements (C, N, O, etc.) introduced during the smelting and heat treatment processes on material performance can be ignored.
[0027] The manufacturing steps of the high entropy austenitic stainless steel are as follows: (1) Based on the design ratio of the chemical components, each raw material was weighed and mixed (the purity of each raw material was ≥ 99.9%), and the mixture was heated in an argon arc furnace at 5.0 × 10 -3 Fill the furnace with argon gas at a pressure of 5.0×10 Pa or less. 3 After the pressure is adjusted to Pa, the oxygen and nitrogen contents in the furnace are less than 0.002% within 180 minutes. First, melt 35g of pure Ti and deoxidize it before starting the melting process. Melt it five times in an argon arc furnace and cast it into a sheet-shaped ingot of 60×10×5mm. The chemical composition of the ingot is the same as that of the high-entropy austenitic stainless steel mentioned above. (2) The above ingot is placed in a furnace to undergo solution treatment and homogenization treatment, and then heated to 1150°C at a rate of 15°C / min, kept at that temperature for 120 minutes, and then water quenched. The ingot after solution treatment is subjected to a cold rolling deformation process. The rolling process is as follows: the reduction in each pass does not exceed 0.2mm, and the total reduction is 66.7%. The rolled ingot is heated to 1145°C at a rate of 18°C / min, kept at that temperature for 1.5 minutes to complete recrystallization. The ingot after recrystallization is heated to 600°C at a rate of 12°C / min, kept at that temperature for 1 hour, and then water quenched to complete the aging treatment.
[0028] Example 4 This embodiment provides a high entropy austenitic stainless steel, the chemical composition of which is as follows: Fe 31 Cr 24 Ni 34 Ti6Al5 (atomic ratio) or Fe 32.08 Cr 23.12 Ni 36.98 Ti 5.32 Al 2.5 (weight ratio), and the effect on the material properties of very small amounts of impurity elements (C, N, O, etc.) that are inevitably mixed in during the smelting and heat treatment processes can be ignored.
[0029] The manufacturing steps of the high entropy austenitic stainless steel are as follows: (1) Based on the design ratio of the chemical components, each raw material was weighed and mixed (the purity of each raw material was ≥ 99.9%), and the mixture was heated in an argon arc furnace at 5.0 × 10 -3 Fill the furnace with argon gas at a pressure of 5.0×10 Pa or less. 3 After the pressure is adjusted to Pa, the oxygen and nitrogen contents in the furnace are less than 0.002% within 180 minutes. First, melt 40g of pure Ti and deoxidize it before starting the melting process. Melt it five times in an argon arc furnace and cast it into a sheet-shaped ingot of 60×10×5mm. The chemical composition of the ingot is the same as that of the high-entropy austenitic stainless steel mentioned above. (2) The above ingot is placed in a furnace to undergo solution treatment and homogenization treatment, and then heated to 1150°C at a rate of 15°C / min, kept at that temperature for 120 minutes, and then water quenched. The ingot after solution treatment is subjected to a cold rolling deformation process. The rolling process is as follows: the reduction in each pass does not exceed 0.2mm, and the total reduction is 66.7%. The rolled ingot is heated to 1155°C at a rate of 10°C / min, kept at that temperature for 1.5 minutes to complete recrystallization. The ingot after recrystallization is heated to 600°C at a rate of 10°C / min, kept at that temperature for 1 hour, and then water quenched to complete the aging treatment.
[0030] Example 5 This embodiment provides a high entropy austenitic stainless steel, the chemical composition of which is as follows: Fe 42 Cr 16 Ni 28 Ti7Al7 (atomic ratio) or Fe 43.88 Cr 15.56 Ni 30.75 Ti 6.27 Al 3.53 (weight ratio), and the effect on the material properties of very small amounts of impurity elements (C, N, O, etc.) that are inevitably mixed in during the smelting and heat treatment processes can be ignored.
[0031] The manufacturing steps of the high entropy austenitic stainless steel are as follows: (1) Based on the design ratio of the chemical components, each raw material was weighed and mixed (the purity of each raw material was ≥ 99.9%), and the mixture was heated in an argon arc furnace at 5.0 × 10 -3 Fill the furnace with argon gas at a pressure of 5.0×10 Pa or less. 3 After the pressure is adjusted to Pa, the oxygen and nitrogen contents in the furnace are less than 0.002% within 180 minutes. First, melt 35g of pure Ti and deoxidize it before starting the melting process. Melt it six times in an argon arc furnace and cast it into a sheet-shaped ingot of 60×10×5mm. The chemical composition of the ingot is the same as that of the high-entropy austenitic stainless steel mentioned above. (2) The above ingot is placed in a furnace to undergo solution treatment and homogenization treatment, and then heated to 1150°C at a rate of 15°C / min, kept at that temperature for 120 minutes, and then water quenched. The ingot after solution treatment is subjected to a cold rolling deformation process. The rolling process is as follows: the reduction in each pass does not exceed 0.2mm, and the total reduction is 66.7%. The rolled ingot is heated to 1160°C at a rate of 20°C / min, kept at that temperature for 1.5 minutes to complete recrystallization. The ingot after recrystallization is heated to 600°C at a rate of 10°C / min, kept at that temperature for 1 hour, and then water quenched to complete the aging treatment.
[0032] Example 6 This embodiment provides a high entropy austenitic stainless steel, the chemical composition of which is as follows: Fe 49 Cr 16 Ni 28 Ti4Al3 (atomic ratio) or Fe 49.9 Cr 15.17 Ni 29.98 Ti 3.49 Al 1.48 (weight ratio), and the effect on the material properties of very small amounts of impurity elements (C, N, O, etc.) that are inevitably mixed in during the smelting and heat treatment processes can be ignored.
[0033] The manufacturing steps of the high entropy austenitic stainless steel are as follows: (1) Based on the design ratio of the chemical components, each raw material was weighed and mixed (the purity of each raw material was ≥ 99.9%), and the mixture was heated in an argon arc furnace at 5.0 × 10 -3 Fill the furnace with argon gas at a pressure of 5.0×10 Pa or less. 3 After the pressure is adjusted to Pa, the oxygen and nitrogen contents in the furnace are less than 0.002% within 180 minutes. First, melt 30g of pure Ti and deoxidize it before starting the melting process. Melt it six times in an argon arc furnace and cast it into a sheet-shaped ingot of 60×10×5mm. The chemical composition of the ingot is the same as that of the high-entropy austenitic stainless steel mentioned above. (2) The above ingot is placed in a furnace to undergo solution treatment and homogenization treatment, and then heated to 1150°C at a rate of 15°C / min, kept at that temperature for 120 minutes, and then water quenched. The ingot after solution treatment is subjected to a cold rolling deformation process. The rolling process is as follows: the reduction in each pass does not exceed 0.2mm, and the total reduction is 66.7%. The rolled ingot is heated to 1150°C at a rate of 10°C / min, kept at that temperature for 1.5 minutes to complete recrystallization. The ingot after recrystallization is heated to 600°C at a rate of 10°C / min, kept at that temperature for 1 hour, and then water quenched to complete the aging treatment.
[0034] Experimental Example The materials produced in Examples 1 to 6 were randomly sampled and analyzed, and their yield strength R eL , tensile strength R m , elongation at break E, yield ratio (R eL / R m The statistical analysis results are shown in Table 1, of which each sample in the table was detected three times and random sampling was used. [Table 1] (1) As can be seen from Table 1, the high entropy austenitic stainless steels manufactured according to Examples 1 to 3 of the present invention have higher yield strength and tensile strength, and the elongation at break is maintained at a high level. The yield ratio is within a reasonable range of 0.67 to 0.73. In Examples 4 and 5, the Ti and Al contents are excessive, so brittle intermetallic compounds are formed, and although the strength is improved, there is a lot of plastic loss. In Example 6, the Ti and Al contents are insufficient, so precipitation strengthening cannot be maximized, and the strength is low. (2) Figure 3 shows the engineering stress-strain curve of high-entropy austenitic stainless steel measured at room temperature. The strain rate used was 1×10 -3 s -1The yield strength, tensile strength and fracture elongation of high entropy austenitic stainless steel are shown in Table 1, which shows that the high entropy austenitic stainless steel with optimal performance has a yield strength of 820 MPa, a tensile strength of 1220 MPa and a fracture elongation of 37%. (3) Figure 4 shows the yield strength R of the commercial stainless steel performance in the prior art and the mechanical performance of the high entropy austenitic stainless steel of the present invention. eL and fracture elongation E. As is clear from the figure, the high-entropy austenitic stainless steel of the present invention has a higher yield strength than most commercial stainless steels and retains high plasticity, with the product of the yield strength and fracture elongation being 14.5 to 30.3 GPa%, which is higher than the yield strength of commercial stainless steels, 2.62 to 17.2 GPa%. (4) Figure 5 shows the tensile strength R of the commercial stainless steel performance in the prior art and the mechanical properties of the high entropy austenitic stainless steel of the present invention. m and the fracture elongation E. As is clear from the figure, the high-entropy austenitic stainless steel of the present invention retains high plasticity while at the same time having a higher tensile strength, with the product of the tensile strength and fracture elongation being 18.0 to 46.1 GPa%, which is higher than the 2.9 to 42.8 GPa% of commercial stainless steels. (5) Figure 6 shows a comparison of the yield strength and strength-ductility balance (tensile strength x fracture elongation) of the mechanical properties of the high-entropy austenitic stainless steel of the present invention with the performance of commercial stainless steels in the prior art. As is clear from the figure, the yield strength and strength-ductility balance of the high-entropy austenitic stainless steel of the present invention are higher than those of the stainless steels of the prior art, and it has high strength while retaining high plasticity, and its overall performance is superior to that of the stainless steels of the prior art.
[0035] Obviously, the above examples are provided for clarity of explanation, and are not intended to limit the embodiments. Those skilled in the art may make other different modifications or changes based on the above description. It is not necessary to cover all the embodiments here. Such obvious modifications or variations are still within the scope of protection of the present invention.
Claims
1. Based on atomic percentage content, the elemental composition of stainless steel is: Cr: 5 to 20%; Ni: 5 to 30%; Ti: 6 to 15%; Al: 5 to 15%; The balance is Fe, The yield ratio is 0.67 to 0.73, The size of the nano-precipitate phase in the stainless steel is 30 nm or less, and the number density of the nano-precipitate phase is 5.0×10 21 m −3 or more. A high entropy austenitic stainless steel.
2. The method is characterized in that the raw materials are mixed according to the atomic ratio requirements, and an ingot is obtained by melting and pouring in a vacuum argon arc furnace, and the ingot is solution treated, and then (1) undergoes cold rolling and recrystallization, or (2) undergoes hot rolling, cold rolling, recrystallization, and then undergoes aging treatment, thereby precipitating nano-precipitate phases having a size of 30 nm or less and a number density of 5.0 x 1021 m-3 or more in a high-entropy austenitic stainless steel, Based on atomic percentage content, the elemental composition of the stainless steel is: Cr: 5 to 20%; Ni: 5 to 30%; Ti: 6 to 15%; Al: 5 to 15%; The balance is Fe, A method for producing a high entropy austenitic stainless steel having a yield ratio of 0.67 to 0.
73.
3. In the cold rolling process in (1), the reduction amount of each pass does not exceed 0.2 mm, and the total reduction amount is 60% to 70%; The method according to claim 2 .
4. The hot rolling and cold rolling process in (2) above, Hot rolling is performed at 800°C to 1150°C, the reduction of each pass does not exceed 0.5mm, and the temperature during hot rolling is guaranteed to be within the 800-1150°C range. When the temperature drops, it can be returned to the furnace and kept warm within the rolling temperature range for 5-15 minutes. After the total reduction is 50%-60%, the cold rolling process is switched on, and the reduction of each cold rolling pass does not exceed 0.2mm, and the total reduction is 60%-70%. The method according to claim 2 .
5. The specific operation of the recrystallization is to keep the rolled ingot at 1140°C to 1160°C for 1 to 3 minutes in (1) or (2), The heating rate of the recrystallization is 10° C. / min to 20° C. / min. The method according to claim 2 .
6. In the smelting process in the vacuum argon arc furnace, the argon arc furnace is 5.0 × 10 -3 Argon gas was filled in the furnace to a pressure of 5.0 x 10 Pa or less. 3 After the temperature is adjusted to Pa, if the oxygen content and nitrogen content in the furnace are both less than 0.002% within 180 minutes, melting is started. Furthermore, the method further includes removing oxygen with pure Ti before starting melting, The number of melting cycles in the vacuum argon arc furnace is at least four; The method according to claim 2 .
7. The specific procedure of the solution treatment is as follows: After pouring, the ingot is 1.0 x 10 -3 Heat to 1140°C to 1160°C at 0.02 Pa or less, hold for 1 to 2.5 hours, then water quench or cool in air; The heating rate of the solution treatment is 10° C. / min to 20° C. / min. The method according to claim 2 .
8. The specific procedure of the aging treatment is as follows: The recrystallized ingot is kept at 500°C to 600°C for 0.5 to 1.5 hours, then water quenched or air cooled. The temperature rise rate of the aging treatment is 5° C. / min to 15° C. / min. The method according to claim 2 .
Citation Information
Patent Citations
Super steel reinforced by precipitation of nano intermetallic compound, and preparation method for same
CN110408850A
Austenitic stainless steel and automotive exhaust system paprts
JP2001059141A
High-strength austenitic stainless steel for high-pressure hydrogen gas
JP2014047409A
Stainless steel
JP2018095929A
Nickel-iron-aluminum-chromium based alloys, and products made therefrom
US20190024225A1
